Peran Guru Pendidikan Agama Dalam Menanamkan Nilai Moderasi Beragama Siswa - egi (Yayasan Al-Afif, 2024)
Indonesia is a pluralistic society consisting of various ethnic and national religions and various colors of language adorning Indonesia. So it is very easy for him to be divided. At this time there is a lot of information on social media related to violence. Moderation in Islam is called wasatiyyah which teaches its people to spread justice, kindness and tolerance for every difference. Educational institutions or schools play an important role in building religious moderation. So that students' understanding of religion is not narrow, education needs to teach broad and non-personal religious knowledge. In this thesis, a qualitative descriptive approach is used. This research is a type of field research. The location of this research is at SMK Negeri 1 Garut, Jawabarat Province. Data collection techniques used interviews, observation and documentation. Data validity test using triangulation of sources and techniques. The role of Islamic Religious Education Teachers in instilling the values of religious moderation of students at SMK Negeri 1 Garut is as a conservator (preserver), Innovator (developer), Transmitter (successor), transformer (translator) and organizer (organizer). The values of religious moderation instilled in SMK Negeri 1 Garut are the values of ta'aruf (getting to know each other), tasamuh (tolerance), tarahum and ta'awun (compassion and help), tawassuth (middle attitude), i'tidal (fair), and shura (deliberation).